A Prospective Trial of Withdrawal and Reinstitution of Ursodeoxycholic Acid in Pediatric Primary Sclerosing Cholangitis. Issue 11 (29th August 2019) - Black, Dennis D.; Mack, Cara; Kerkar, Nanda; Miloh, Tamir; Sundaram, Shikha S.; Anand, Ravinder; Gupta, Ashutosh; Alonso, Estella; Arnon, Ronen; Bulut, Pinar; Karpen, Saul; Lin, Chuan‐Hao; et al.
Abstract : Ursodeoxycholic acid (UDCA) is commonly used to treat several liver disorders in adults and children, including primary sclerosing cholangitis (PSC) for which it is not U.S. Food and Drug Administration approved. UDCA treatment has an uncertain impact on disease outcomes and has been reported in high doses to be associated with worse outcome in adults with PSC. In this context, controlled withdrawal and reintroduction of UDCA in children with PSC were studied. Prior to study initiation, participants were required to have alanine aminotransferase (ALT) and gamma‐glutamyl transpeptidase (GGT) <2 times the upper limit of normal on stable UDCA dosing. The study included four phases: I (stable dosing), II (50% UDCA reduction), III (UDCA discontinuation), IV (UDCA reintroduction), with a primary endpoint of change in ALT and GGT between phases I and III. We enrolled 27 participants (22 completed) between March 2011 and June 2016. Changes in mean ALT and GGT between phases I and III were ALT, +29.5 IU/L ( P  = 0.105) and GGT, +60.4 IU/L ( P  = 0.003). In 7 participants, ALT and GGT ≤29 IU/L did not rise above 29 IU/L (null response group). Eight participants had increases of ALT or GGT >100 IU/L (flare group). None developed elevated bilirubin. All flares responded to UDCA reinstitution. Serum GGT, interleukin‐8, and tumor necrosis factor α levels were higher in the flare group at baseline. Liver biochemistries increased in children with PSC during controlled UDCA withdrawal; one third increased above 100 IU/L and one third remained normal during UDCA withdrawal. Conclusion : The impact of prolonged UDCA use in childhood PSC and the significance of a biochemical flare are unclear. Further studies of the natural history and treatment of pediatric PSC and UDCA use are needed. Abstract :